2002
DOI: 10.1539/joh.44.226
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electromagnetic Field on Free‐Radical Processes in Steelworkers. Part I: Magnetic Field Influence on the Antioxidant Activity in Red Blood Cells and Plasma

Abstract: Effects of Electromagnetic Field on Free‐ Radical Processes in Steelworkers. Part I: Magnetic Field Influence on the Antioxidant Activity in Red Blood Cells and Plasma: Bogusfaw Kula, et al. Department of Experimental and Clinical Biochemistry, Silesian School of Medicine, Poland—The purpose of the study was the evaluation of electromagnetic field (electric field strength of 20 V/ m, f=50 Hz and magnetic field strength of 2 A/m, f=50 Hz) effects on the antioxydative activity in steelworkers’ red blood cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 12 publications
2
10
0
Order By: Relevance
“…Many observations have been reported which indicate the increase in free radicals as a result of lipid peroxidation. MDA is the byproduct of such peroxidation, and it increases in amount too [13]. Our results confirm these observations.…”
Section: Malondealdehyde Contentsupporting
confidence: 90%
See 1 more Smart Citation
“…Many observations have been reported which indicate the increase in free radicals as a result of lipid peroxidation. MDA is the byproduct of such peroxidation, and it increases in amount too [13]. Our results confirm these observations.…”
Section: Malondealdehyde Contentsupporting
confidence: 90%
“…A number of studies have shown that abiotic stress can cause alterations in the structure and composition of lipids in the plasma membrane. An example for such alterations can be the increase in free sterols, which leads to a decrease in the fluidity of the cell membrane [13]. In this study, MDA content increased significantly in plants that were treated for longer durations with EMF ( Figure 1).…”
Section: Malondealdehyde Contentmentioning
confidence: 52%
“…Similarly, Kula and his colleagues investigated the effect of electromagnetic fields on workers in the steel industry for 3-10 years. In the study data, it is seen that there is an increase in the plasma MDA level with the increase of the study period according to the control group [13]. In our study, it was observed that the MDA level was higher in the high voltage group than in the control group.…”
Section: Discussionsupporting
confidence: 49%
“…There are various studies in which the effect of magnetic field on free radical metabolism has been investigated [31,32]. Kula et al [31] reported that cytosolic MDA levels increased significantly in both liver and kidney of female and male rats exposed to the ELF magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…Kula et al [31] reported that cytosolic MDA levels increased significantly in both liver and kidney of female and male rats exposed to the ELF magnetic field. Watanabe et al [14] measured lipid peroxidation, in liver, kidney, heart, lung and brain of mice exposed to static magnetic field.…”
Section: Discussionmentioning
confidence: 99%